20-hydroxyecdysone stimulation of juvenile hormone biosynthesis by the mosquito corpora allata. (September 2015) - Areiza, Maria; Nouzova, Marcela; Rivera-Perez, Crisalejandra; Noriega, Fernando G.
Abstract: Juvenile hormone III (JH) is synthesized by the corpora allata (CA) and plays a key role in mosquito development and reproduction. JH titer decreases in the last instar larvae allowing pupation and metamorphosis to progress. As the anti-metamorphic role of JH comes to an end, the CA of the late pupa (or pharate adult) becomes again "competent" to synthesize JH, which plays an essential role orchestrating reproductive maturation. 20-hydroxyecdysone (20E) prepares the pupae for ecdysis, and would be an ideal candidate to direct a developmental program in the CA of the pharate adult mosquito. In this study, we provide evidence that 20E acts as an age-linked hormonal signal, directing CA activation in the mosquito pupae. Stimulation of the inactive brain- corpora allata - corpora cardiaca complex (Br-CA-CC) of the early pupa (24 h before adult eclosion or −24 h) in vitro with 20E resulted in a remarkable increase in JH biosynthesis, as well as increase in the activity of juvenile hormone acid methyltransferase (JHAMT). Addition of methyl farnesoate but not farnesoic acid also stimulated JH synthesis by the Br-CA-CC of the −24 h pupae, proving that epoxidase activity is present, but not JHAMT activity. Separation of the CA-CC complex from the brain (denervation) in the −24 h pupae also activated JH synthesis. Our results suggest that an increase in 20E titer might override an inhibitory effect of the brain on JH synthesis, phenocopying denervation. All together these findings provide compelling evidence that 20E acts as a developmental signal that ensures proper reactivation of JH synthesis in the mosquito pupae. Graphical abstract: Highlights: 20-hydroxyecdysone (20E) stimulates juvenile hormone (JH) synthesis by the corpora allata (CA) of the early pupae. The CA of early pupae has a large amount of farnesoic acid (FA), but little methyl farnesoate (MF). The CA of early pupae is deficient in juvenile hormone acid methyl transferase activity (JHAMT). Treatment with 20E stimulates JHAMT activity that catalyzes the conversion of FA into MF. 20E acts as a "derepressor", overriding the inhibitory action of the brain.